Exploring Space and Place in Literature: Towards Digital Analysis and Literary Mapping in the Context of Latvian Cultural History - Kalnačs, Benedikts; Daija, Pauls (Colloquia, 2019)
This paper focuses on the digital analysis of Latvian novels (46 in total) published between 1900 and 1914. By elaborating this corpus of texts and detecting and scrutinizing different facets of space representation, we ask questions in regard to the possibilities, as well as potential predicaments of the use of the methodology of digital humanities when applied to the interpretation of literary texts. We are especially interested in the representations of enlargement of geographical space in the novels and the ways in which the literary representations are linked to historical and social events. In the final part, , we discuss how the outcomes of digital analysis play a part in the process of canon-building in Latvian literature, and what similarities and differences prevail in texts included in the literary canon and in those remaining on the periphery. The conclusion further relates these issues to the nationbuilding process of the nineteenth- and early twentieth-century Latvia.